Intestinal permeability to polyethylene glycol 400 in patients with Crohn's disease - Ruttenberg, David (Department of Medicine, 2017)
An altered small intestinal permeability has been proposed as an important aetiological factor in the pathogenesis of inflammatory bowel disease. The relevant literature was reviewed. Intestinal permeability to Polyethylene glycol 400 in patients with Crohn' s disease, their relatives and healthy controls was examined and the data compared with studies of small bowel permeability to other similar sized probes. A new technique of analysis of urinary Polythylene Glycol 400 by High Performance Liquid Chromatography was described and compared with a previously established HPLC method. No evidence of an altered bowel permeability could be found using Polyethylene glycol 400, but the possibility that this may have been related to probe size and characteristics can not be excluded .